Pediatric cardiac services in Sudan: Achievements, challenges, and future perspectives (2004–2021) - Ali, Sulafa; Medani, Mohamed Eamin A.M.E. (Frontiers in Pediatrics, 2022)
Pediatric cardiology is a rapidly advancing specialty addressing a large population of children. It requires huge technical and financial resources both for diagnostic and treatment aspects. Establishing, maintaining and developing such services in limited resource settings are challenging. A program for pediatric cardiology that included clinical aspects, echocardiography, diagnostic and interventional cardiac catheterization and cardiac surgery was established in Sudan in 2004. There are currently 3 centers with facilities to evaluate and treat children with heart disease: 2 in Khartoum and one in Wad Medani. Major obstacles include the shortage of trained personnel and surgical slots, deficiency of intensive care facilities, training and retention of staff as well as financial burden of surgical procedures. This paper details the establishment and progress of the program, the challenges facing it and actions needed to overcome these challenges.